Aural toilet (ear cleaning) for chronic suppurative otitis media - Bhutta, M; Head, K; Chong, L; Tu, N; Schilder, A; Burton, M; Brennan-Jones, C (Cochrane Collaboration, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of aural toilet procedures for people with chronic suppurative otitis media.